An Archivist and a Records Manager: Professional Education in Ukraine (Case study of the National Aviation University) - Tiurmenko, Iryna; Bozhuk, Liudmyla (Knygotyra, 2020)
A higher education reform in Ukraine, and the emergence of the new integrated program “Information, Library and Archival Studies” instead of “Records Management and Information Activity” in the educational space in particular, brought about various interpretations and sharp discussions. In general, the university community met these innovations without enthusiasm. The scientific thought of Ukrainian scholars on how to develop archival education in Ukraine was generally based on the tradition enshrined in the complex of the developed academic disciplines and tested in practice in conditions of intense competition among students.The approach of the Department of History and Records Management of the National Aviation University to modern training of the archivist was prompted by the needs of the labor market and the challenges of the digital society.1 It consists of finding ways to train modern specialists who possess interdisciplinary competences in the field of archival studies, records management, information activity, and socio-communicative sciences. This led to a study aimed at finding an up-to-date profile of a records manager/archivist.The research analyzes the approaches to the education of archivists in Ukraine at various stages of its socio-economic development and summarizes the current experience of the National Aviation University in this sphere.
Keywords: archival science; study program 029 “Information, Library and Archival Studies”; competent specialist; Higher Education Institutions of Ukraine; National Aviation University (NAU)